2016
DOI: 10.1038/nature17970
|View full text |Cite
|
Sign up to set email alerts
|

Near-atomic resolution visualization of human transcription promoter opening

Abstract: In eukaryotic transcription initiation, a large multi-subunit pre-initiation complex (PIC) that assembles at the core promoter is required for the opening of the duplex DNA and identification of the start site for transcription by RNA polymerase II. Here we use cryo-electron microscropy (cryo-EM) to determine near-atomic resolution structures of the human PIC in a closed state (engaged with duplex DNA), an open state (engaged with a transcription bubble), and an initially transcribing complex (containing six b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
385
1
3

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(416 citation statements)
references
References 95 publications
(144 reference statements)
27
385
1
3
Order By: Relevance
“…Surprisingly, in the Pol I PIC, the upstream DNA duplex follows a remarkably different path (Fig 2C). In the Pol II PIC, the upstream DNA is bound outside of the cleft by several transcription factors (Murakami et al , 2015; He et al , 2016; Plaschka et al , 2016), whereas in the Pol I PIC, the upstream DNA is positioned closer to the wall and protrusion domains. Moreover, upstream DNA in the Pol I elongation complex (EC) re‐anneals close to the protrusion domain and the positive helix (Tafur et al , 2016), while in the Pol I PIC, the upstream DNA is even closer to the wall and to the A135 “wedge” (residues 813–819; Barnes et al , 2015; Fig EV2A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, in the Pol I PIC, the upstream DNA duplex follows a remarkably different path (Fig 2C). In the Pol II PIC, the upstream DNA is bound outside of the cleft by several transcription factors (Murakami et al , 2015; He et al , 2016; Plaschka et al , 2016), whereas in the Pol I PIC, the upstream DNA is positioned closer to the wall and protrusion domains. Moreover, upstream DNA in the Pol I elongation complex (EC) re‐anneals close to the protrusion domain and the positive helix (Tafur et al , 2016), while in the Pol I PIC, the upstream DNA is even closer to the wall and to the A135 “wedge” (residues 813–819; Barnes et al , 2015; Fig EV2A).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the C‐terminal cyclin domain of Rrn7 is not positioned as closely to the DNA as in Pol II, where the C‐terminal cyclin domain of TFIIB contacts DNA upstream of the TATA box (Plaschka et al , 2016). The observed differences could be a result of DNA bending by TBP in the Pol II PIC, which brings the DNA in close proximity to the C‐terminal cyclin domain (Murakami et al , 2013, 2015; Plaschka et al , 2015, 2016; He et al , 2016). Nevertheless, the overall conformation of the C‐terminal cyclin domain relative to the N‐terminal cyclin domain is conserved between TFIIB‐like factors (Fig 3C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…"Now we have to start adding in the regulation," she says, by incorporating a multitude of molecules that affect transcription. She notes that her laboratory has already visualized a preinitiation complex with more than 30 proteins in several functional states (9).…”
Section: Intractable Subjectmentioning
confidence: 99%
“…It has also been shown that scrunching in RNAP helps to determine the exact DNA base from which to begin transcription (Robb et al 2013;Winkelman et al 2016). Recent cryo-EM structures of human PICs show breaks in electron density on the nontemplate DNA strand in the RP itc , and this was proposed to be disordered due to possible scrunching within RP itc (He et al 2016). Thus, it appears that scrunching could be a universal scanning mechanism in both prokaryotes and eukaryotes that helps position the correct starting base in the catalytic center of polymerase.…”
mentioning
confidence: 99%